2004
DOI: 10.1080/00672700409480384
|View full text |Cite
|
Sign up to set email alerts
|

The potential for Historical Archaeology in the Sudan

Abstract: IntroductionTraditional archaeologies of the Middle Nile and the modern Sudan have long-focused on the more obvious and monumental achievements of its early "civilizations". The archaeology of more recent periods, however, remains largely neglected; such work as has been undertaken has tended to be framed simply in terms of an "Islamic" archaeology, in succession to a "Christian" medieval archaeology. What this paper wishes to explore is the possibility of developing some rather different approaches to the arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
4
3
0
Order By: Relevance
“…Leveraging previously-published genome-wide data from three ancient Egyptians, we show that the West Eurasian-related ancestry detected at Kulubnarti was plausibly introduced via people from Egypt who harbored a majority of Western Eurasian-related ancestry and a minor proportion of Nilotic-related ancestry. The introduction of West Eurasian-related ancestry through Egypt is consistent with archaeological evidence of connections between Egypt and the Levant established by the first half of the 4 th millennium BCE 74,75 and between Egypt and Nubia ongoing since at least the second half of the 3 rd millennium BCE 1-4,76,77 . Archaeological and strontium isotope studies have identified Egyptian occupation as far as southern Upper Nubia 4,76,78,79 and have uncovered well-established cultural and material links between Nubia and the Ptolemaic and Roman Egyptian and Hellenistic worlds existing alongside indigenous cultural traditions rooted in Sudanic Africa 76,80 .…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Leveraging previously-published genome-wide data from three ancient Egyptians, we show that the West Eurasian-related ancestry detected at Kulubnarti was plausibly introduced via people from Egypt who harbored a majority of Western Eurasian-related ancestry and a minor proportion of Nilotic-related ancestry. The introduction of West Eurasian-related ancestry through Egypt is consistent with archaeological evidence of connections between Egypt and the Levant established by the first half of the 4 th millennium BCE 74,75 and between Egypt and Nubia ongoing since at least the second half of the 3 rd millennium BCE 1-4,76,77 . Archaeological and strontium isotope studies have identified Egyptian occupation as far as southern Upper Nubia 4,76,78,79 and have uncovered well-established cultural and material links between Nubia and the Ptolemaic and Roman Egyptian and Hellenistic worlds existing alongside indigenous cultural traditions rooted in Sudanic Africa 76,80 .…”
Section: Discussionsupporting
confidence: 75%
“…The introduction of West Eurasian-related ancestry through Egypt is consistent with archaeological evidence of connections between Egypt and the Levant established by the first half of the 4 th millennium BCE 74,75 and between Egypt and Nubia ongoing since at least the second half of the 3 rd millennium BCE 1-4,76,77 . Archaeological and strontium isotope studies have identified Egyptian occupation as far as southern Upper Nubia 4,76,78,79 and have uncovered well-established cultural and material links between Nubia and the Ptolemaic and Roman Egyptian and Hellenistic worlds existing alongside indigenous cultural traditions rooted in Sudanic Africa 76,80 . Studies of skeletal morphology 61,81 and genetic studies of present-day populations 52 suggest long-term interactions between Egypt and Nubia involving gene flow.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Studies of cranial and dental traits suggest that the Kulubnarti Nubians were similar to ancient people from Wadi Halfa, located to the north near the Nile’s Second Cataract 8 , 9 ; however, morphological data have limited resolution for determining biological relationships relative to genome-wide data. Genetic studies of present-day Nubians reveal a mix of sub-Saharan African- and West Eurasian-related ancestry, but the mixture is largely a result of the Arab conquest of the late-1st and early-2nd millennia CE 20 , a time during which people with West Eurasian-related ancestry spread southward along the Nile through Egypt and into Nubia 1 , 4 . Because more recent admixture events obscure our understanding of the ancestry of people who predate these events, the analysis of paleogenomic data from Kulubnarti offers an opportunity to directly investigate the ancestry and biological relationships of a Nubian group that lived in the region before the introduction of Islam.…”
Section: Introductionmentioning
confidence: 99%